Internal Short Circuit Protection for Rotor Winding of Variable Speed Pumped-Storage Generator-Motor - Jun CHEN; Hong YE; Huazhong LI; Jianchun LI; Xiaogang CHEN; Kai WANG (Zhongguo dianli)
To provide a solution to the imperfect protection problem of variable speed pumped-storage units when the rotor winding has internal short circuit faults, a stator-side branch circulation current based protection method is proposed for internal short circuit of AC excitation motor rotor winding. Based on the multi-loop theory, the key technologies for internal short circuit protection are studied in terms of digital filter design, protection criteria, error prevention measures. A protection prototype is developed and a dynamic simulation experiment platform is established for its verification. The experimental results show that the proposed method can reliably reflect the inter-turn and phase-phase short-circuit faults of the rotor winding. The protection devices developed based on the method will be applied in a variable speed pumped storage unit in China.